Extract of varieties of guava (Psidium guajava L.) leaf modulate angiotensin-1-converting enzyme gene expression in cyclosporine-induced hypertensive rats - Leye Jonathan Babatola; Ganiyu Oboh (Elsevier, 2021)
Background: Hypertension has become a serious health problem with which people have to live day by day, it sometimes results in severe organ damage with a dead end. Management with Psidium guajava L. (guava) leaf extract through modulation of angiotensin-converting enzyme (ACE) mRNA expression would give succor to patients with hypertension. However, there are several reports on medicinal efficacy of guava leaf with dearth of information on its varieties. Hypothesis: Elevation of the ACE mRNA level in the kidney plays a primary role in the acceleration of local angiotensin II formation and thus sustain hypertension. Studies have shown the significance of investigating the molecular mechanism of ACE activities in pathophysiological states, this work sought to investigate the modulatory effect of aqueous extract of leaf from different varieties of guava on ACE mRNA gene expression in cyclosporine-induced hypertensive rats. Methods: Hypertension was induced via intraperitoneal (i.p) administration of cyclosporine (25mg/kg/day); an aqueous extract of leaves from white, red, and pink guava was prepared, 250 and 500mg/kg body weight of the extracts were administered to the rats by oral gavage for 7 days. The systolic (SBP) and diastolic (DBP) blood pressure was measured, ACE mRNA expression level was determined using RT-qPCR, with kidney function markers in plasma (creatinine, urea, and uric acid), plasma nitric oxide level, the kidney histopathology, as well as phenolic characterization of the guava leaves. Results: The results showed a significant (p<0.05) increase in SBP, DBP, plasma creatinine, urea, and uric acid concentration, as well as nitric oxide level with up-regulation of ACE gene expression in the rats' kidneys with severe glomerular damage, necrosis, and capillary collapse. However, a significant (p<0.05) down-regulation of ACE mRNA expression level, reduced serum creatinine, urea, and uric acid concentration with mild-moderate kidney damage was observed in the treated rats. The leaves extract characterization and quantification revealed chlorogenic acid, rutin, vanillic acid, and quercetin as the most abundant phenolic compounds in the leaves. Conclusions: The oral administration of the aqueous extract of different varieties of guava leaf (rich in phenolics), reduced SBP, DBP, kidney function markers concentration in the plasma, with increased plasma nitric oxide level, ameliorate kidney damage, and down-regulate renal ACE gene expression with no significant (p>0.05) difference in activities of extracts from different varieties of guava leaves used for this study. This could be a useful therapeutic measure for the treatment/management of hypertension.